PENGEMBANGAN FORUM DISKUSI KULIAH ONLINE MAHASISWA PENDIDIKAN FISIKA UNIVERSITAS NEGERI SEMARANG - Sudarwati, Ida; Khanafiyah, Siti; Sugiyanto, Sugiyanto (UPEJ Unnes Physics Education Journal, 2017)
Students of Physics Education of Semarang State University often find it difficult to understand the lecture material. During difficult times, students usually find references on the internet, ask a friend who already understand, or ask to the senior. Students have a device that can be used to access the internet. Online lectures discussion forum can be used as a discussion facility when they find it difficult to understand the lecture material. Online lectures discussion forum developed with ADDIE development model that includes the stages of analysis, design, development, implementation, and evaluation. Online lectures discussion forum contains the list of courses that can be accessed by students via the Internet through the website diskusi.belajarfisika.web.id. Feasibility of online lectures discussion forum was measured through assessment sheets of feasibility test from validators and questionnaire responses from students. The results of the feasibility test from validator and student responses indicate that criteria are eligible. Results of the questionnaire about students' perceptions of learning through online lectures discussion forum show that physics educations students of Semarang State University have good perceptions of learning through online lectures discussion forums.